Caccioppoli-type estimates for a class of nonlinear differential operators - Tiryaki, A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish Caccioppoli-type estimates for a class of nonlinear differential equations with the aid of a differential identitythat generalizes the well-known multidimensional Picone’s formula. In special cases, these estimates give the Finsler $p$-Laplacian, the $p$-Laplacian and the pseudo-$p$-Laplacian.